Perceived work ability index of public service employees in relation to ageing and gender: A comparison in three European countries - Pranjic Nurka; Gonzales Juan Manuel Garcia; Cvejanov-Kezunović Ljiljana (Sciendo, 2019)
Increasing longevity raised the prospect of a workplace for ageing workers. Previous studies reveal that work ability decreases with age, even among the healthy, and decreased significantly with age among women. The aim of the study is to examine the perception of work ability of public sector employees aged 55 years and older and gender differences in three European countries.